Inisiasi Ketangguhan Masyarakat dalam Mengatasi Adiksi NAPZA: Menelaah Program Rehabilitasi - Maria Goretti Adiyanti (Buletin Psikologi, 2019)
The problem of drug abuse and addiction cannot yet be resolved completely even though many addicts have done rehabilitation. This paper aims to analize intervention programs for drug addicts and propose alternative programs that emphasize psychological aspects. This paper begins by interpreting the implementation of the Drug Rehabilitation Center Practice and relaps after the addict completes rehabilitation. An understanding of addiction is needed to provide an understanding of the mental state of addicts and the process of change that must be experienced during the rehabilitation process. The recovery process through the Rehabilitation Institution will be discussed, especially in achieving "clean and sober" conditions. At the end of the article an alternative of psychological growth program is presented as a complementary program with the exsisting TC program. Psychological growth programs are expected to have a contribution to overcome psychological problems that until now have not been addressed